Perkembangan Kebijakan Kurikulum Pendidikan Diniyah Formal - Voullin Hamzah; Dede Rosyada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Formal Diniyah Education (PDF) is a subsystem of the national education system and represents a religious education pathway in the form of madrasah within the scope of Islamic boarding school education (pesantren). Formal Diniyah Education (PDF) is an Islamic religious education program offered at pesantren and operates in a tiered formal education pathway. This education is officially conducted under a tiered structure consisting of elementary, secondary, and higher education levels. This writing employs a literature study method by collecting data from various sources such as books, articles, journals, and relevant archives. PDF policies ensure that students in formal institutions receive the same services as students in other institutions. Formal diniyah education offers educational programs that include general education as well as Islamic education based on the classical Islamic texts (kutub al-turats). To achieve the desired goals, an evaluation of the PDF curriculum is necessary. This evaluation includes the Balance of Religious and General Education, Teaching Quality and Teachers, Curriculum Implementation, Evaluation and Assessment Standards, Life Skills Development, Government Support and Budget Allocation, and Curriculum Innovation.